Climate policy options and the World Trade Organization - Gary Clyde Hufbauer; Jisun Kim (Kiel Institute for the World Economy (IfW), 2009)
This paper examines whether the climate policy options policymakers are contemplating are compatible with core principles of the world trading system set forth in the General Agreement on Tariffs and Trade (GATT), the World Trade Organization (WTO), and Appellate Body decisions. The authors argue that border measures both import restrictive measures and export subsidies contemplated in US climate bills and the climate policies of other countries stand a fair chance of being challenged in the WTO. Given the prospect of foreseeable conflicts with WTO rules, the authors suggest that key WTO members should attempt to negotiate a new code that delineates a large 'green space' for measures that are designed to limit GHG emissions both within the member country and globally. By 'green space,' the authors mean policy space for climate measures that are imposed in a manner broadly consistent with core WTO principles even if a technical violation of WTO law could occur. To encourage WTO negotiating efforts along these lines, the authors recommend a time-limited 'peace clause' to be adopted into climate legislation of major emitting countries. The peace clause would suspend the application of border measures or other extraterritorial controls for a defined period while WTO negotiations are under way.
Keywords: 330; Global warming climate change; climate policy options; world trading system; world trade organization; WTO; border measures; Klimaschutz; Internationale Umweltpolitik; WTO-Regeln; Internationale Handelspolitik; Welt